The pedestrian behaviour scale: A systematic review of its validation around the world. (February 2022) - Vandroux, Romane; Granié, Marie-Axelle; Jay, Mathilde; Sueur, Cédric; Pelé, Marie
Highlights: This review of the evolution uses and validation of the PBS supports road safety research. Analysis of differences in validation enable researchers' methodological choices. Dimensions for future research such as positive behaviours are identified. Abstract: Objective: The Pedestrian Behaviour Scale (PBS) is a self-report questionnaire that distinguishes five dimensions of pedestrian behaviour: violations, errors, lapses, aggressive behaviours and positive behaviours. This study aimed to meet three objectives: to trace the development of the PBS worldwide from 1997 to 2021, to report on its varied uses and to analyse the scientific validation of the different dimensions of pedestrian behaviour reflected by the PBS and its derivatives. Design/methodology: In this systematic literature review, we selected all works that cited the 2013 founding study of the PBS as well as all publications that cited the 2017 US validation of PBS which was frequently replicated around the world. We conducted an online database search using Web of Science, Google Scholar, ResearchGate and PubMed. After excluding duplicates, 116 studies were identified. A total of 30 studies were selected to meet our first two objectives and 14 studies were selected to meet our third objective. Results: Over time, the PBS has undergone many changes. Overall, we found differences in the scientific validation of this questionnaire depending on the version used, the validation tests performed and the population studied. The original version of the PBS and its Turkish adaptation proved most appropriate for assessing the transgressions dimension. The American version of the PBS proved a suitable alternative but it is more suited to assessing the two independent dimensions of violations and errors. The Chinese version of the PBS (CPBS) proved unsuitable for assessing the lapses dimension, while the original version of the PBS emerged as the best option for assessing aggressive behaviours. The positive behaviour dimension presented many validation difficulties but its assessment by the CPBS seems to be the most appropriate option. Conclusion: As no systematic review of the PBS has been conducted before, researchers can now make an informed choice of methodology quickly and be guided by our recommendations regarding the use and possible improvements of the different validated versions.